6.
Пошаговое объяснение:
√ (6+5х) = х
(√(6+5х))^2 = х^2
6+5х = х^2
0 = х^2 - 5х - 6
а = 1; b = - 5; c = - 6.
D = b^ - 4ac = (-5)^2 -4•1•(-6) = 49
x1 = (5+7)/2 = 6;
x2 = (5-7)/2 = - 1;
Проверка:
Если х = 6, то
√ (6+5•6) = 6; √36 = 6; 6=6 - верно.
6 является корнем.
Если х = -1, то
√ (6+5•(-1) )= -1; √1 = -1; 1=-1 - неверно.
-1 не является корнем.
6.
Пошаговое объяснение:
√ (6+5х) = х
(√(6+5х))^2 = х^2
6+5х = х^2
0 = х^2 - 5х - 6
а = 1; b = - 5; c = - 6.
D = b^ - 4ac = (-5)^2 -4•1•(-6) = 49
x1 = (5+7)/2 = 6;
x2 = (5-7)/2 = - 1;
Проверка:
Если х = 6, то
√ (6+5•6) = 6; √36 = 6; 6=6 - верно.
6 является корнем.
Если х = -1, то
√ (6+5•(-1) )= -1; √1 = -1; 1=-1 - неверно.
-1 не является корнем.